Differential expression of circulating microRNAs in lactating Holstein and Jersey cows exposed to heat stress - Jihwan Lee; Doosan Kim; Byeonghwi Lim; Gyeonglim Ryu; Hyeonguk Baek; Joohwan Kim; Seungmin Ha; Sangbum Kim; Seunghwan Lee; Taejeong Choi; Inchul Choi (Journal of Animal Reproduction and Biotechnology)
Background: South Korea has recently faced record-high temperatures, which have adversely affected dairy production. Holstein cows, the primary dairy breed globally, are particularly sensitive to heat stress. In contrast, Jersey cows have shown greater heat tolerance, as demonstrated by phenotypic studies. Methods: We investigated physiological and molecular responses to heat stress in Holstein and Jersey cows by measuring rectal temperature, milk yield, and average daily gain, confirming Holstein cows’ greater vulnerability. To explore molecular mechanisms, we analyzed circulating microRNA profiles from whole blood samples collected under heat stress and normal conditions using microRNA-sequencing. Differential expression patterns were compared between the two breeds to identify biological pathways associated with heat stress. Results: Four microRNAs (bta-miR-20b, bta-miR-1246, bta-miR-2284x, and bta-miR- 2284y) were significantly differentially expressed in both breeds under heat stress (|FC| ≥ 2, p < 0.05). Notably, bta-miR-20b and bta-miR-1246 were linked to corpus luteum function and progesterone biosynthesis, while bta-miR-2284x and bta-miR- 2284y were associated with immune responses. A comparison of 11 potential heat stress-related microRNAs identified in previous studies of Holstein cows revealed consistent expression trends in Jersey cows, albeit with lower fold changes, suggesting their superior heat resilience. Conclusions: Our study highlights the physiological and microRNA-based differences in heat stress responses between Holstein and Jersey cows. Jersey cows exhibited greater resilience, supported by more stable microRNA expression profiles and improved heat stress indicators, making them a promising breed for dairy production in increasingly hot climates.